Possibilities of application of augmented reality in different branches of education (Educational Dimension, 2020)
Augmented reality has a great impact on the student in the presentation of educational material: objects of augmented reality affect the development of facial expressions, attention, stimulate thinking, and increase the level of understanding of information. Its implementation in various spheres has indisputable advantages: realism, clarity, application in many industries, information completeness and interactivity. That is why the study presents the possibilities of using augmented reality in the study of mathematics, anatomy, physics, chemistry, architecture, as well as in other fields. The comparison of domestic and foreign proposals for augmented reality is presented. The use of augmented reality in various fields (technology, entertainment, science and medicine, education, games, etc.) should be well thought out and pedagogically appropriate. That is why in the future it is planned to conduct research on the feasibility of using augmented reality and to develop elements of augmented reality accordingly.